The night agent. Season one [videorecording (DVD)]. - Basso, Gabriel, 1994-; Buchanan, Luciane; Evans-Akingbola, Fola; Desjardins, Sarah, 1994-; Harlow, Eve, 1989-; Raei, Phoenix; Murciano, Enrique, 1973-; Woodside, D. B. (David Bryan), 1969- (Sony Pictures Home Entertainment, 2024)
Low-level FBI agent Peter Sutherland works in the basement of the White House manning a phone that never rings - until the night it does, propelling him into a conspiracy that leads all the way to the Oval Office.